Single-site laparoscopic-assisted surgery for congenital intestinal atresia - Zeng, Shan; Zhong, Bin; Shu, Fang; Zhang, Peng; Wu, Shuqing (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate the efficacy and safety of single-site laparoscopy in the management of congenital intestinal atresia. Method: The retrospective study was conducted from January to December 2024 at the Ganzhou Maternal and Child Health Care Hospital, China, and comprised data from January 2014 to December 2023 related to paediatric patients with congenital intestinal atresia who underwent surgical intervention. The patients were divided into laparotomy group A and laparoscopic group B. The two groups were compared in terms of general data, operating time, intraoperative blood loss, time-to-diet, length of hospital stay and postoperative complications. Data was analysed using SPSS 26. Results: Of the 120 patients, 64(53.3%) were in group A; 40(62.5%) boys and 24(37.5%) girls with median age 3.0 years (interquartile range: 2.0-4.8 years). The remaining 56(46.7%) patients were in group B; 32(57.1%) boys and 24(42.9%) girls with median age 3.0 years (interquartile range: 2.0-4.0 years) (p>0.05). Group B had increased operating time and intraoperative blood loss, and reduced postoperative complications compared to group A (p<0.05). There was no significant intergroup difference in terms of time-to-diet and length of hospital stay (p>0.05). Conclusion: Single-site laparoscopy was found to be a viable approach for treating neonatal congenital intestinal atresia, it was associated with a reduced incidence of postoperative complications. Key Words: Newborn, Intestinal atresia, Laparoscopy, Laparotomy, Paediatrics.